The Relationship between Ethical Climate and Organizational Citizenship Behavior of Nurses in Selected Hospitals Affiliated to Shahid Beheshti University of Medical Sciences - Ehsan Zarei; Soheila Damiri; Ali Bagheri; Farasat Fazli Ouchhesar (Kerman University of Medical Sciences, 2019)
The Relationship between Ethical Climate and Organizational Citizenship Behavior of Nurses in Selected Hospitals Affiliated to Shahid Beheshti University of Medical Sciences   Zarei Ehsan1, Damiri Soheila2, Bagheri Ali2, Farasat Fazli Ouchhesar3* 1. Assistant Professor, Department of Health Policy Management and Economics, School of Management and Medical Education, Shahid Beheshti University of Medical Sciences, Tehran, Iran 2. MSc Student of Health Service Management, School of Management and Medical Education, Shahid Beheshti University of Medical Sciences, Tehran, Iran 3. MSc of Health Service Management, Shariate Hospital, Tehran, Iran *Correspondence: Shariati Hospital, North Kargar Ave, Tehran Tel: 00982177878589                                               Email: fazli.farasat66@gmail.com           Abstract: Background & Objectives: Ethical values act as the most powerful factors influencing citizenship behaviors. This research was conducted to investigate the relationship between ethical climate and organizational citizenship behavior in nurses of hospitals affiliated to Shahid Beheshti University of Medical Sciences. Methods: This descriptive-analytical study was performed on 307 nurses selected through random sampling in 2016. Data gathering tools were two questionnaires of ethical climate and organizational citizenship behavior. Data analysis was done through SPSS20 and using descriptive statistics, t-test, One- Way ANOVA, correlation and multiple regression tests. Results: Mean scores of ethical climate and citizenship behavior were respectively 3.51 ±0.55 and 3.49 ± 0.45 that reflects the favorable view of nurses towards ethical climate and citizenship behavior. Head nurses had the highest mean scores in the dimensions of ethical climate. Among the dimensions of citizenship behavior, the dimension of conscience gained the highest mean score among nurses. There was a significant relationship between employment status and ethical climate (P<0.001) and also a positive and significant correlation between ethical climate and citizenship behavior (P<.0.001). Conclusion: Promotion of ethical climate enables nurses to respond better to ethical stress, to adapt to other causes of workplace dissatisfaction and consequently showing citizenship behaviors. Some meetings are required to be held in order to improve the relationship between physicians and nurses, to create alignment and understanding among staff and consequently to improve citizen behaviors.     Keywords: Ethical climate, Organizational citizenship behavior, Nurses, Teaching hospital   Citation: Zarei E, Damiri S, Bagheri A, Fazli Ouchhesar F. The Relationship between Ethical Climate and Organizational Citizenship Behavior of Nurses in Selected Hospitals Affiliated to Shahid Beheshti University of Medical Sciences. Journal of Health Based Research 2019; 5(2): 175-186. [In Persian]